Comparative Analysis of the Use of State Management in E-commerce Marketplace Applications Using the Flutter Framework - Akhmad Dinan Jatnika, Aditya; Akbar, Muhammad Aminul; Pinandito, Aryo (Faculty of Computer Science (FILKOM) Brawijaya University, 2023)
This research aims to analyze the performance of two popular state management tools that have different system approaches, namely Riverpod and GetX, in developing marketplace applications using the Flutter framework. The marketplace type application used is Flutter ecommerce which is available as open source on the GitHub platform. This research aims to provide benefits to Flutter application developers in choosing the right state management tools for marketplace applications. The method used is to compare memory usage, execution time and CPU utilization of the two tools. Testing is done on the feature of displaying the home screen, search and add features. The results of the analysis obtained are that there are differences in memory usage and execution time for the three features and scenarios, GetX provides less memory usage with faster execution time. While in CPU utilization, there tends to be no performance difference between GetX and Riverpod. The conclusion is that GetX state management uses memory more efficiently and is able to provide faster execution time than Riverpod state management with better performance.